2015
DOI: 10.1016/j.envsoft.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating uncertainties of future marine flooding occurrence as sea-level rises

Abstract: International audienceAs sea-level rises, the frequency of coastal marine flooding events is changing. For accurate assessments, several other factors must be considered as well, such as the variability of sea-level rise and storm surge patterns. Here, a global sensitivity analysis is used to provide quantitative insight into the relative importance of contributing uncertainties over the coming decades. The method is applied on an urban low-lying coastal site located in the north-western Mediterranean, where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 72 publications
2
72
0
Order By: Relevance
“…While it is desirable to specify statistical uncertainty ranges for some parameters, this may not always be possible. The longer the planning timeframe, the increasing dominance of SLR on the outcome [45], and neither a best estimate, nor statistical uncertainty, can be robustly derived for SLR [18,29]. In any case the optimal risk will occur at a higher SLR than the best estimate of the hazard, due to the tail in the probability distribution for SLR for any of the RCPs [12].…”
Section: How Certain Are We? Uncertainty Is Importantmentioning
confidence: 99%
See 2 more Smart Citations
“…While it is desirable to specify statistical uncertainty ranges for some parameters, this may not always be possible. The longer the planning timeframe, the increasing dominance of SLR on the outcome [45], and neither a best estimate, nor statistical uncertainty, can be robustly derived for SLR [18,29]. In any case the optimal risk will occur at a higher SLR than the best estimate of the hazard, due to the tail in the probability distribution for SLR for any of the RCPs [12].…”
Section: How Certain Are We? Uncertainty Is Importantmentioning
confidence: 99%
“…Additionally, Le Cozannet et al [45] showed that the relative importance of the various sources of uncertainties changes over the time-local coastal processes such as storm-tide and wave runup are the most important during the first part of this century, whereas uncertainties of future SLR scenarios largely dominate beyond the year 2080. In other words, level 2 statistical uncertainty is relatively important over short-term planning timeframes (before year 2060), but after a transition period (2060-2080), level 3-5 scenario and deep uncertainties become dominant over longer planning timeframes (after the year 2080), driven mainly by the increasing uncertainty in the rates of SLR [45].…”
Section: How Certain Are We? Uncertainty Is Importantmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative importance of the sources of uncertainties change over the time: local coastal processes are the most important during the first part of this century, whereas uncertainties of future SLR scenarios largely dominate beyond 2080 [12]. Statistical uncertainty is relevant over short-term planning timeframes (≤ 2050), but after a transition period, scenario and deep uncertainties become dominant over longer planning timeframes (≥ 2080), driven mainly by the increasing uncertainty in the rates of SLR up to and beyond 2100 [9,12].…”
Section: How Certain Are We? Uncertainty Is Importantmentioning
confidence: 99%
“…For coastal flooding, uncertainty relates not only to the amount or rate of sea-level rise (SLR) and socio-economic development, but also to the input data used in the analysis. While scenario uncertainty is generally explored in coastal impact assessments, data uncertainty has not received as much attention in the literature (Le Cozannet et al, 2015). Initial work carried out (Lichter et al, 2011;Mondal and Tatem, 2012) has shown that variations in estimates of area and population exposure are highly dependent on the input datasets.…”
Section: Introductionmentioning
confidence: 99%